(untitled) (Research, Society and Development, 2025)
The production of brandy in Mozambique is a traditional practice with great economic and social relevance, usually carried out in an artisanal and rudimentary manner, with little technical or scientific basis. The most commonly used raw materials include sugarcane, corn and sorghum, which are subjected to spontaneous fermentation and subsequently distilled in stills that are often built with inadequate materials. As a consequence of this process, a final product is obtained without standardization, with low food safety and little knowledge regarding its chemical composition. Given this scenario, the present study sought to analyze the physical-chemical parameters of three distilled spirits produced from corn bran in the province of Inhambane, southern Mozambique, comparing them with the limits established by Brazilian legislation for cachaças and other spirits. The samples were collected and sent to the Quality Analysis Laboratory of Brandy of the Chemistry Department (LAQA/DQI) of the Federal University of Lavras, Minas Gerais, Brazil. The analyses were performed in accordance with the specifications established by Normative Instruction No. 24 of September 8, 2005 of the Ministry of Agriculture, Livestock and Food Supply (MAPA). The results show that the spirits produced in Mozambique from fermentation with corn bran do not meet the requirements established by current Brazilian legislation for alcoholic beverages. These results highlight the urgent need for new studies on the production of spirits in Mozambique, seeking the introduction of technical knowledge, use of appropriate equipment and application of good manufacturing practices that ensure the quality and safety of the beverage for the consumer.